The Lunar Cycle: Effects of Full Moon on Renal Colic - Molaee Govarchin Ghalae, Hojjat; Zare, Samad; Choopanloo, Maryam; Rahimian, Roya (Urology Journal, 2011)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –> Purpose: To evaluate renal colic frequency in different seasons and around full moon. Materials and Methods: A total of 1481 patients with renal colic were studied retrospectively addressing days of a month both in solar and lunar calendar. Results: The mean age of the patients was 57 ± 13 years. Total admissions in summer was 613; of which 288 (41%), 199 (39%), and 126 (43%) were in years 2002, 2003, and 2004, respectively. The highest frequencies in solar calendar were on days 2 (56), 20 (63), and 27 (59) and the lowest were on days 6 (36), 22 (38), 26 (34), and 31 (31). We did not find any statistically significant association according to solar calendar (P = .3). In lunar calendar, most of the admissions were on day 15 (69) and the lowest rates were on days 1 (25) and 30 (26), which was statistically significant (P = .04). Conclusion: Renal colic frequency is not correlated with solar calendar, but its highest frequency in lunar calendar is in the middle of the month period. Although we found a correlation between full moon effect and renal tide, but this is a new window for further studies.